Performance Assessment and Personality Evaluation When Starting a Career - Garai, Anna (European Journal of Sustainable Development, 2017)
For the young generation about to start a career it is vital to get a joint or independent assessment on performance and personality. Compared to previous generations the young people’s attitudes towards assessment and evaluatuion processes are completely different. Older generations have got the experience of the firm and unflexible assessment systems at education and workplaces. They were ready to accept these decisions, although not only the performance but also the performer was evaluated. The process of value judgement is the most contraversial and problematic human function, as the ability to distinguish between right and wrong is a basic criterium of human existence, and a clear warning in each period in the history of culture: do not judge. Is it possible to make an assessment without any evaluation? We must assume that young career entrants are aware of this dichotomy. They see the importance of distinguishing between good and bad performance but they find it possible only by excluding judgement on personality. Our aim is to examine career entrants’ attitude in the frame of a survey study. Keywords: perfomance evaluation, evaluation of personality, value judgement analysis, survey, career entrants